2015
DOI: 10.7763/ijssh.2015.v5.503
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Administrators in Distance Education Programme: A Case at Higher Learning Institutions

Abstract: Abstract-This study examined the role of administrators in facilitating instructors and students of distance education programme (DEP) to the use of effective communication tools of the present digitized environment. Administrators/coordinators of DEP were purposively selected from three different universities in Malaysia. Their responses from interviews had been transcribed and coded. Students' feedback and monitoring activities on Learning Management System (LMS) were also collected and analyzed. Findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hashim et al [23] reported that when asked about future plans for improving distance education programs administration, administrators said that training helped lecturers to become more proficient at delivering content. Hashim et al [23] recommended improving communication practices among lecturers and attitudes toward effective online instruction, which are critical for ensuring distance learners success.…”
Section: Managing Distance Educationmentioning
confidence: 99%
“…Hashim et al [23] reported that when asked about future plans for improving distance education programs administration, administrators said that training helped lecturers to become more proficient at delivering content. Hashim et al [23] recommended improving communication practices among lecturers and attitudes toward effective online instruction, which are critical for ensuring distance learners success.…”
Section: Managing Distance Educationmentioning
confidence: 99%
“…Hashim, Kayode and Hassan [22] investigated distance learning administrators of the three selected universities manage, monitors and improve communication and interactions between distance learning instructors and learners to promote self-regulated learning. The results of the study showed methods used by the administrators (1) suitable teaching qualification, (2) monitoring of forum activities (3) feedbacks (4) taking care of learning platform, and ( 5) training.…”
Section: Literature Reviewmentioning
confidence: 99%